Peran Pendidikan Kewarganegaraan dalam Membangun Identitas Nasional - Azil hanifa azzahra; Najmi Nawry; Sasmi Nelwati (Universitas Maritim AMNI Semarang, 2024)
Civic Education (PKn) plays an important role in shaping national identity in the midst of a diverse society. This study aims to explore how PKn in schools contributes to the development of national identity, understand the challenges faced, and identify effective strategies in the implementation of the PKn curriculum. The results of the study show that PKn can strengthen the sense of nationality and national unity, but also requires adjustment to face the social and cultural dynamics that continue to develop.